2015
DOI: 10.1186/s12943-015-0408-z
|View full text |Cite
|
Sign up to set email alerts
|

Epiregulin contributes to breast tumorigenesis through regulating matrix metalloproteinase 1 and promoting cell survival

Abstract: BackgroundThe epidermal growth factor (EGF) family of ligands has been implicated in promoting breast cancer initiation, growth and progression. The contributions of EGF family ligands and their receptors to breast cancer are complex, and the specific mechanisms through which different ligands regulate breast tumor initiation and growth are not well-defined. These studies focus on the EGF family member epiregulin (EREG) as a mediator of early stage breast tumorigenesis.MethodsEREG expression levels were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 39 publications
(51 reference statements)
2
26
0
Order By: Relevance
“…MMPs are involved in breakdown of the extracellular matrix, tissue healing, and remodeling (Martins et al 2013; Nagase and Woessner 1999). In this study, MMP1 was the most up-regulated gene, and examination of EREG-induced signaling pathways has demonstrated that EREG promotes cell survival through regulating the expression of MMP1 (Boström et al 2011; Farooqui et al 2015). Our results also suggest that MMP1 has a strong ability to promote cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 85%
“…MMPs are involved in breakdown of the extracellular matrix, tissue healing, and remodeling (Martins et al 2013; Nagase and Woessner 1999). In this study, MMP1 was the most up-regulated gene, and examination of EREG-induced signaling pathways has demonstrated that EREG promotes cell survival through regulating the expression of MMP1 (Boström et al 2011; Farooqui et al 2015). Our results also suggest that MMP1 has a strong ability to promote cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 85%
“…In the cytoplasm, lncRNAs regulate gene expression mainly at post-transcriptional level. On the one hand, lncRNAs can facilitate mRNA decay, stabilize mRNAs, and promote or inhibit the translation of target mRNAs through extended base-pairing [ 20 ]. On the other hand, lncRNAs can also function as the microRNAs precursor or compete for microRNA-mediated inhibition, as is the case for the competing endogenous RNAs (ceRNA) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…We further demonstrated that CUZD1 is recruited along with pSTAT5 to the regulatory regions of key target genes, such as Ereg and Wap . It is plausible that EREG contributes to CUZD1-mediated epithelial proliferation and alveolar expansion during pregnancy and lactation, as Ereg is a direct transcriptional target of STAT5 and has been implicated in promoting growth and survival of breast cancer cells [4042]. …”
Section: Discussionmentioning
confidence: 99%